Physical Examination Is Predictive of Cauda Equina Syndrome: MRI to Rule Out Diagnosis Is Unnecessary. Issue 2 (March 2022) - Zusman, Natalie L.; Radoslovich, Stephanie S.; Smith, Spencer J.; Tanski, Mary; Gundle, Kenneth R.; Yoo, Jung Uck
Study Design: Cross-sectional cohort study. Objectives: Cauda equina syndrome (CES) is a neurologic emergency, and delay in diagnosis can result in irreversible impairment. Our purpose was to determine the value of physical examination in diagnosis of CES in patients complaining of bladder and/or bowel complications in the emergency department. Methods: Adult patients at one tertiary academic medical center that endorsed bowel/bladder dysfunction, underwent a lumbar magnetic resonance imaging (MRI), and received an orthopedic spine surgery consultation from 2008 to 2017 were included. Patients consulted for trauma or tumor were excluded. A chart and imaging review was performed to collect demographic, physical examination, and treatment data. Sensitivity, specificity, and negative and positive predictive values were calculated, and fast-and-frugal decision trees (FFTs) were generated using R. Results: Of 142 eligible patients, 10 were diagnosed with CES. The sensitivity and specificity of the exam findings were highest for bulbocavernosus reflex (BCR) (100% and 100%), followed by rectal tone (80% and 86%), postvoid residual bladder (80% and 59%), and perianal sensation (60% and 68%). The positive predictive value was high for BCR (100%), but low for other findings (13% to 31%). However, negative predictive values were consistently high for all examinations (96% to 100%). Two FFTs utilizing combinations of voluntary rectal tone, perianal sensation, and BCR resulted in no false negatives. Conclusions: A combination of physical examination findings of lower sacral function is an effective means of ruling out CES and, with further study, may eliminate the need for MRI in many patients reporting back pain and bowel or bladder dysfunction.